Scale and discontinuity (Estudios Sociales, 2020)
From reflection on the uses of observation scales in the Historiography, as of those proposed by Microhistory to the approaches of Global History, the text questions the ways in which historiographical narration has reconstructed different social processes–for instancethe development of the modern State, the rural exodus, industrialization and urbanization- recovering thearguments that questions their necessary and universal character. This analytical exercise allows pointing out how the rescue of the discontinuities and mismatches between the different levels of historical matter constitutes a critical instrument against the simplifying evidence of the reality of the historical world.
Keywords: scales; discontinuity; historiography